Study of Stunting Financing Handling in Dosay Health Center, West Sentani District, Jayapura Regency - Anggai, Martapina; Tingginehe, Rosmin Mariati (PT FORMOSA CENDEKIA GLOBAL, 2024)
There are 3 important nutritional problems that occur in Indonesia, namely: poor nutrition (stunting and wasting); nutritional problems of overweight and obesity; and micronutrient deficiency problems (anemia, vitamin A deficiency, and iodine deficiency). The aim of this research is to examine the handling of stunting financing at the Dosay Community Health Center. Data collection was carried out through interviews with the nutrition program manager of the Jayapura District Health Service and the nutrition program management at the Dosay Community Health Center, as well as representatives from the community, a total of 11 informants. The results of this research state that the beneficiaries of the stunting financing program are pregnant women, breastfeeding mothers and children aged 0-49 months. The funding allocation for handling stunting financing at the Dosay Community Health Center in 2020 was 741,632,500, increasing in 2021 to 832,928,000 and in 2022 decreasing to 755,233,000.